SOIL SEED BANK IN SEASONAL SEMIDECIDUOUS FOREST AND ABANDONED PASTURE - Kunz,Sustanis Horn (2016)
ABSTRACT The objective of this study was to characterize the seed bank in the soil of different successional stages of Seasonal Semideciduous Forest and abandoned pasture in order to understand the natural regeneration potential of these areas. At each successional stage, 30 samples of soil were collected in the rainy and dry seasons to evaluate the qualitative heterogeneity of the forest, at the regeneration stage (FEA) forest, intermediate regeneration stage forest (ISF) and pasture (PAS). The species were classified according to the life form, successional group and dispersion syndrome. The number of individuals germinated was significantly higher (p < 0.001) in the ISF and in the rainy season (15,949 individuals). Richness was higher in the pasture area (79 species), with a significant difference only between the environments. Most species are herbaceous (49.5%), pioneers (76.5%) and zoocory was the main dispersion syndrome (49% of species). The results show that seed bank in the fragment of the regeneration advanced stage forest presents the highest resilience potential, since it is formed by different life forms and, mainly, by early and late secondary species.